Porównawcze metody wyceny nieruchomości a model ekonometryczny - Pawlukowicz, Roman (Comparative approaches towards property valuation and the econometric model, 2007)
The current range of property valuation methods in Poland is finalised. It is limited by legal sources (acts and regulations). One method of property valuation is the comparative approach. It can be applied utilising three alternative methods: pair comparison, average price adjustment, and statistical market data analysis. The following paper focuses on the effect of transforming these methods procedural operations - written in words in legal regulations and professional standards - info the form of characteristic of them interdependencies. The obtained results are compared to the effects obtained by the use of econometric modelling, which leads to the conclusion that the comparative approach - in each of the three methods - is a simulation formed on the basis of the econometric model.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1189, s. 124-133